Influence of the anodization electrical mode on the final properties of electrocolored and sealed anodic films prepared on 1050 aluminum alloy - Regone, Natal Nerímio [UNESP]; Casademont, Christophe; Arurault, Laurent (My University, 2022)
The present study focused on the preparation of colored coatings on 1050 aluminum substrate using a four-step process including pretreatments, anodization, electrocoloring and hydrothermal sealing. Anodization of aluminum susbtrates can be usually performed either in potentiostatic mode or galvanostatic mode. The aim here was to study the influence of the electrical anodization mode (ideally with similar film thicknesses) and the influence of the alternating voltage applied during subsequent coloring on the final coating properties (color, hardness and anti-corrosion performance). Scanning electron microscopies (SEM and FEG-SEM) were used to obtain surface and cross-sectional views of the final coatings, and estimate the average pore diameter, while layer thicknesses (i.e. barrier, porous and sealing layers) were evaluated using different analytical techniques. Final coatings properties (i.e. hardness, color, electrical and corrosion resistance) were then studied. In particular, corrosion resistance was analyzed by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization. For both electrical anodization modes, similar coating thicknesses were obtained experimentally, while average pore diameter of the anodic films were of the same order of magnitude. For each electrical anodization mode, deeper color was obtained for optimum coloring voltage. However, the deeper colors obtained were associated with the lower coating hardness. Furthermore, based on total resistance values, coatings resulting from galvanostatic anodization have enhanced corrosion resistance than samples prepared by potentiostatic anodization. However, EIS analysis agreed with the results shown by polarization curves, highlighting that in such experimental conditions, coloring using high alternating voltage can be detrimental to the anticorrosion properties of such coatings.
Keywords: Aluminum; Anodization; Electrocoloring; Galvanostatic mode; Potentiostatic mode